Giovanna Valverde, IPCC WGIII release, April 16 2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Costa Rica's Zero Emissions Policy and agricultural NAMAs for coffee and livestock -- Giovanna Valverde, Ministry of Agriculture and Livestock, Costa Rica Meeting global food needs with lower emissions: IPCC report findings on climate change mitigation in agriculture A dialog among scientists, practitioners and financiers April 16, 2014 World Bank, Washington, DC